Zambia Health Sector Public Expenditure Tracking and Quantitative Service Delivery Survey - Chansa, Collins; Matsebula, Thulani; Piatti, Moritz; Mudenda, Dale; Chama-Chiliba, Chitalu Miriam; Chitah, Bona; Kaonga, Oliver; Mphuka, Chris (World Bank, Washington, DC, 2019)
Zambia’s health sector has continued to evolve with the government undertaking several reforms aimed at improving the performance of the sector to achieve the Sustainable Development Goals (SDGs) and their precursor, the Millennium Development Goals (MDGs). Amid the ongoing reforms, the health sector has recorded a number of achievements, but some challenges remain. This Public Expenditure Tracking and Quantitative Service Delivery Survey (PET-QSDS) assesses the financing and delivery of health services, and whether the reform objectives have been made. This was achieved by reviewing the flow of financial and other resources in the public health sector from administrative units to service delivery points at the facility level. The data were collected from administrative units, health workers, and patients to gauge the various dimensions of the health system that include financial flows, management of infrastructure, human resources for health, and patient management. Specifically, the issues which were reviewed are: Availability, adequacy, and timeliness of resources for service delivery; implementation of some key policy reforms such as user fee removal and adherence to policy guidelines; donor resource coordination, ownership, and fragmentation at the district level; assessment of human resources management at the district and facility levels; and comparison of staff satisfaction, absenteeism, and service delivery in districts implementing the Results-based Financing (RBF) model and non-RBF districts.